New answers tagged


The formula is $$d = 6\,n - \sum_{i= 1}^{J}\left( 6 - f_i\right)$$ or $$d = 6N - 1 - \sum_{i=1}^j\ (6 - f_i) = 6(N-1 - J) + \sum_{i=1}^J\ f_i $$ In the book Modern Robotics, there is an additional (-1) in the formula, as shown in the second version of the formula, as they recommend counting the ground as linkage. I do not count ground as linkage, I do not ...


I was able to figure out after digging further through several other posts and google searches. This post pointed me in the right direction: Then Wikipedia:

Top 50 recent answers are included